NEW AEROGEOPHYSICAL STUDY OF THE EURASIA BASIN AND LOMONOSOV RIDGE: IMPLICATIONS FOR BASIN DEVELOPMENT - Brozena J.M.; Childers V.A.; Lawver L.A.; Gahagan L.M. (My University, 2003)
In 1998 and 1999, new aerogeophysical surveys of the Arctic Ocean's Eurasia Basin produced the first collocated gravity and magnetic measurements over the western half of the basin. These data increase the density and extend the coverage of the U.S. Navy aeromagnetic data from the 1970s. The new data reveal prominent bends in the isochrons that provide solid geometrical constraints for plate reconstructions. Tentative identification of anomaly 25 in the Eurasia Basin links early basin opening to spreading in the Labrador Sea before the locus of spreading in the North Atlantic shifted to the Norwegian-Greenland Sea. With the opening of the Labrador Sea, Greenland began 200 km of northward movement relative to North America and eventually collided with Svalbard, Ellesmere Island, and the nascent Eurasia ocean basin. Both gravity and magnetic data sets reconstructed to times prior to chron 13 show a prominent linear anomaly oriented orthogonal to the spreading center and immediately north of the Yermak Plateau and Morris Jesup Rise. This anomaly may mark the locus of shortening and possibly subduction as Greenland collided with the nascent Eurasia Basin and impinged upon the southern Gakkel Ridge. This collision may have contributed to volcanism on the Morris Jesup Rise. By chron 13, Greenland had ended its northward motion and had become fixed to North America, and the plateau north of Greenland had rifted apart to become the Morris Jesup Rise and the Yermak Plateau. [PUBLICATION ABSTRACT]
Keywords: GEOLOGY; REGIONS; RIVERS